Farmers innovations in print - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
special issue (July 2000, volume 16, no.2) of LEISA Subscription:US$ 25 E 29.30 for 4 issues per year. For organisations in the South subscriptions are free on request. LEISA Subscriptions officer ILEIA Foundation PO Box 64 3830 AB Leusden Nether